2022
DOI: 10.1039/d2fo02268k
|View full text |Cite
|
Sign up to set email alerts
|

Sanghuangporus vaninii mixture ameliorated type 2 diabetes mellitus and altered intestinal microbiota in mice

Abstract: Type 2 diabetes mellitus (T2DM) is a chronic disease mainly caused by insufficient insulin secretion and insulin resistance. In addition, T2DM is often accompanied by dysregulation of lipid metabolism and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…88,90 Additional authors have reported that a Sanghuangporus vaninii mixture ameliorated obesity related type-2 diabetes and altered intestinal microbiota by reducing the abundance of Odoribacter. 91…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…88,90 Additional authors have reported that a Sanghuangporus vaninii mixture ameliorated obesity related type-2 diabetes and altered intestinal microbiota by reducing the abundance of Odoribacter. 91…”
Section: Resultsmentioning
confidence: 99%
“…88,90 Additional authors have reported that a Sanghuangporus vaninii mixture ameliorated obesity related type-2 diabetes and altered intestinal microbiota by reducing the abundance of Odoribacter. 91 Finally, a predictive analysis of the metabolic function of the intestinal microbiota was performed using Tax4Fun (ESI Table 2 †). According to our gene expression analysis data, the prediction confirmed differences in the signalling pathways related to lipid and carbohydrate metabolism.…”
Section: Food and Function Papermentioning
confidence: 99%
“…For this reason, pharmaceutical research has concentrated to identify effective lipid‐lowering drugs which preferably have few side effects. S. vaninii is an edible and medicinal mushroom with various efficacy (Guo et al., 2021 ); its safety and its potential to reduce blood lipid levels make it a likely anti‐hyperlipidemia agent (Huang, Liu, et al., 2022 ; Huo et al., 2020 ). In this study, a high‐fat diet was used to induce hyperlipidemia in rats, who were then treated with SVE to confirm the effects of S. vaninii , with simvastatin as a positive control.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are 14 species in the genus Sanghuangporus and of these S. vaninii is the main species applied in the health care and medical field because it produces higher yields, although the research on its pharmacological properties is not thorough (Guo et al., 2022 ; He et al., 2021 ; Wu & Dai, 2020 ). There are a few reports that S. vaninii has the potential to reduce blood lipids (Huang, Huang, et al., 2022 ; Huang, Liu, et al., 2022 ). However, the underlying anti‐hyperlipidemia mechanism of S. vaninii is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…3.9.0) was performed for the analysis of the visible correlation network. 30 The correlation between bacterial genus and hypoglycemic parameters was calculated by Spearman's rank correlation analysis (| r | > 0.6, FDR adjusted p < 0.01).…”
Section: Methodsmentioning
confidence: 99%